Spiritualitas Kesetiaan dalam Perkawinan Menurut Kitab Amsal 5:15-20 dan Injil Yohanes 4:7-15 - Barnabas Bang; Agustinus M.L. Meko (Sekolah Tinggi Kateketik Pastoral Katolik (STKPK) Bina Insan Keuskupan Agung Samarinda, 2022)
The monogamous and indissoluble nature of marriage is considered irrelevant to individual freedom. This departs from social phenomena that show the existence of ambiguity, confusion, and even mistakes in the meaning of marriage. Through the study and literature review of the Book of Proverbs 5:15-20 and the Gospel of John 4:7-15, it is found that faithfulness and freedom are not contradictory, and the spiritual meaning of fidelity in marriage is found. The perspective of Proverbs 5:15-20 emphasizes fidelity, the key to the joy of marriage. The Gospel of John 4:7-15 confirms the meaning of faithfulness in the Christian family by making Jesus the source of faithfulness. Faithfulness comes from faith in Jesus. Loyalty in the household embodies God's radical love for humans.